MORPHOLOGICAL FEATURES OF THE TRIGEMINAL GANGLION IN ACUTE ASEPTIC INFLAMMATION AT THE EARLY STAGES OF THE EXPERIMENT - Daniliv О.D.; Stetsuk, Ye.V.; Boruta, N.V.; Lukiantseva, G.V.; Shepitko, V.I. (World of Medicine and Biology, 2021)
The phenomena of acute λ-carrageenan inflammation in the trigeminal ganglion were characterized by phasing. Thus, in the first stage, against the background of increasing hydration, minor destructive phenomena in the structure of the stroma of the trigeminal ganglion are revealed, which adversely affect metabolism, resulting in impaired blood circulation, reduced phagocytic response activity. Such changes are observed only in the early stages, which lead to slowing or suppression of the cell barrier formation, with subsequent reactivation and generalization of the process due to inflammatory factors activity in the trigeminal ganglion stroma and in the nervous tissue specifically. The second phase is characterized by regenerative phenomena; the products of tissue metabolism are resorbed or removed from the site of inflammation. All this occurs together with reducing the clinical signs of inflammation, normalization of biochemical and functional disorders that occur in the first phase of inflammation.